2020
DOI: 10.3390/f11010114
|View full text |Cite
|
Sign up to set email alerts
|

Interregional Crown Width Models for Individual Trees Growing in Pure and Mixed Stands in Austria

Abstract: Crown width is a functional trait that is commonly used to improve the estimation of above-ground biomass of forests and is often included as a predictor variable in forest growth models. Most of the existing crown width models reflect the relationship between crown width, tree size and competition variables, but do not consider the effect of species mixture. In this study, we developed crown width models for individual-tree of the major tree species growing in Austria. Because these models should be applicabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 37 publications
0
10
0
3
Order By: Relevance
“…CW-D models are commonly used to predict the crown width of trees ( Buchacher & Ledermann, 2020 ). The models proposed in the current study explain the greatest portion of crown width variation and fully confirm that crown width and DBH are strongly correlated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…CW-D models are commonly used to predict the crown width of trees ( Buchacher & Ledermann, 2020 ). The models proposed in the current study explain the greatest portion of crown width variation and fully confirm that crown width and DBH are strongly correlated.…”
Section: Discussionmentioning
confidence: 99%
“…However, the development of crown width is influenced by numerous factors. In many instances, such CW-D relationships are complex nonlinear processes that are difficult to describe using ordinary parameter models, which may overestimate crown width for crowded stands and underestimate crown width for sparse stands ( Sharma et al, 2017 ; Buchacher & Ledermann, 2020 ). Notably, this is the case regardless of competition inside the stand ( Raptis et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has shown that the crown structure of fruit trees is a major factor affecting fruit harvesting [19][20][21]. A suitable crown structure is conducive to vibration of the tree during mechanical harvesting, which improves harvesting efficiency.…”
Section: Introductionmentioning
confidence: 99%